Neurophysiological Aspects in SARS-CoV-2–Induced Acute Respiratory Distress Syndrome - Vecchio, Eleonora; Gallicchio, Lara; Caporusso, Nicola; Recchia, Valentina; Didonna, Luigi; Pezzuto, Giancarlo; Pisani, Luigi; Petruzzellis, Antonella; Delmonte, Vito; Tamma, Filippo (Frontiers in Neurology, 2022)
Patients with coronavirus disease 2019 (COVID-19) often develop acute respiratory failure and acute respiratory distress syndrome (ARDS) that requires intensive care unit (ICU) hospitalization and invasive mechanical ventilation, associated with a high mortality rate. In addition, many patients fail early weaning attempts, further increasing ICU length of stay and mortality. COVID-19 related ARDS can be complicated by neurological involvement with mechanisms of direct central nervous system (CNS) infection and with overlapping parainfective mechanisms of the peripheral nervous system (PNS). We aimed to evaluate the possible involvement of the brainstem and PNS in patients with COVID-19 related ARDS and difficulty in weaning from mechanical ventilation. We evaluated electroencephalogram (EEG), brainstem auditory evoked potentials (BAEPs), electroneurography of the four limbs and the phrenic nerve in 10 patients with respiratory insufficiency due to Sars-Cov2. All were admitted to intensive care unit and were facing prolonged weaning from mechanical ventilation. All ten patients showed a mild diffuse non-specific slowing of brain electrical activity on the EEG. Four patients had an acute motor axonal neuropathy with absent or reduced amplitude phrenic nerve CMAP while four patients showed impairment of the BAEPs. A patient with peripheral nerve impairment suggestive of Guillain-Barré syndrome (GBS) underwent an intravenous immunoglobulin (IVIg) cycle that led to an improvement in the weaning process and progressive motor improvement. The inclusion of a comprehensive neurological evaluation in COVID-19 patients in ICU facilitated the early identification and effective management of Nervous System involvement.